Upaya Perbaikan Keterlambatan Pengajuan Klaim BPJS Kesehatan Pada Unit Rawat Inap di RSIA Srikandi IBI Jember Tahun 2019 - Elsa Mayori; Atma Deharja; Novita Nuraini; Maya Weka Santi (Politeknik Negeri Jember, 2021)
Based on a preliminary study at RSIA Srikandi IBI Jember, there was a delay in submitting claim health BPJS to the inpatient unit over the next ten months. The delay in submitting claim health BPJS as many as 28 days with 353 inpatient files (57,5%) in January 2019, while February as 31 days with 249 inpatient files (78,3%) and March 29 days with 313 inpatient files (75,0%).It would harm hospital finances because of delays in the payment of health BPJS funds. This research aimed to improve the delay claim of health BPJS in inpatient units at RSIA Srikandi IBI Jember. This research used a qualitative method with interviews, observation, questionnaires, and brainstorming to collect data methods. This research showed that the cause of delay in submitting claims health BPJS by material factor was incomplete inpatient claim such as medical resume, the result of examinations. The Plan made SOP submit requests claims BPJS to the inpatient unit, the checklist of BPJS document, and SOP to verify the completeness and accuracy to the inpatient claim. The Do stage accepts the SOP to the hospital director. Stage of Check is to see the result of implementation claim health BPJS to the inpatient unit in February-April 2020, and that showed a decrease in the number of delays in submitting claims health BPJS at the hospital. Action steps were known that these efforts could help the BPJS health claims process.